Patient participation in dialysis care-A qualitative study of patients' and health professionals' perspectives - Liselott Årestedt; Caroline Martinsson; Carina Hjelm; Fredrik Uhlin; Ann Catrine Eldh (Wiley, 2019)
Abstract Background and objective End‐stage renal disease (ESRD) affects a multitude of aspects in the patient's daily life, often entailing their own involvement in various aspects of the treatment. Although patient participation is a core health‐care value, what the concept signifies is not yet fully known. The purpose of this paper is to conceptualize patient participation in dialysis care, depicting patients' and health‐care professionals' perspectives. Design This explorative study employed qualitative interviews and content analysis. Setting and participants Seven focus group discussions engaging 42 key informants were performed, including patients, staff and managers with experience of dialysis care. Results In dialysis care, patient participation connotes a sharing of information and knowledge, the learning of and planning of care, including partaking in shared decisions with regards to treatment and management, and being involved in the management of one's own health‐care treatment and/or self‐care activities. Although these attributes were illustrated by all stakeholders, their significance varied: patients suggested that their preferences regarding primary aspects of participation vary, while staff considered patients' performance of dialysis to be the ultimate form of participation. Further, while patients considered multiple ways to execute participation, staff suggested that aspects such as sharing information were a route to, rather than actual, involvement. Conclusions Without a common understanding to denote the idea of patient participation, staff and patients are exposed to a potential deficit in terms of facilitating patient participation in everyday encounters of dialysis treatment. Further studies and means to serve a mutual understanding are needed.